School Setting Behavior That Characterizes Social Justice - Ross E. Mitchell; Rodney K. Goodyear; Janee Both Gragg; Philip S. Mirci; Ronald Morgan (SAGE Publishing, 2016)
We used prototype theory to illustrate the concept of social justice in school settings, particularly as it might inform the education of school leaders. Using expert input, we developed descriptions of school setting actions predicted to be perceived as prototypical of social justice in education, as well as of actions that were predicted to be either peripheral or antithetical to the construct. Panels of (a) social justice education faculty and (b) students in social justice-oriented school leadership doctoral programs rated the extent to which each of these resulting 46 actions characterized social justice. Data were analyzed to map the concept.